Determining the Impact of Coastal Flooding on Resident Living in Victoria Island, Lagos State, Nigeria - Ajide, Oyinloye Michael (Modern Advances in Geography, Environment and Earth Sciences Vol. 6, 2021)
Coastal flooding is among the most devastating natural hazards in the world, affecting more people and causing more property damaging than any other natural phenomena. This study was carried out to determine the impact of coastal flooding on resident living in Vitoria Island, Lagos, Nigeria. The objective of this paper is to determine the causes of coastal flooding in Victoria Island area, Lagos State; assess the extent and implications of the coastal flooding at different periods; create a DEM map for the study area using GIS techniques; assess the effects of coastal flooding on the socio-economic characteristics of the residents; and device strategies for managing coastal flooding in the study area. Structural questionnaire and Geographic Information System (GIS) was used to collect the required data for the purpose of fulfilling the objectives of the study. The Coastal flooding of Victoria Island, Lagos was analyzed using topographic map of 1962 and satellite imageries of Landsat TM of 1984, ETM+ 2000 and 2011. Supervised digital image classification method using ILWIS 3.2 and ArcGIS 3.9 was used. The topographic map of 1962 and the imagery of 1984 was glued and crossed; 1984 and 2000; and the 2000 and 2011 were also crossed to get the changes in the shorelines in these years. The results of the analysis reveal that there was loss in landmass between 1962 and 1984 (31.4%) while between 1984-2000 (81.89%) and 2000-2011 (62.11%) there was increase in landmass gain over the periods respectively. To reduce the effect of coastal flooding, the study recommended construction of standard paved surface and drainages, law enforcement on waste disposal, integrated approach to flooding management and control and flood insurance policies. Correlation was used to test the relationship between flooding and refuse disposal. The result shows that there is strong correlation between incidence of flood and poor refuse disposal practices.